(untitled) (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
This paper aim to discuss the data relating to the ornaments of tomb 51 of the necropolis of Strada Santo Stefano in Gravina in Puglia. The burial, in which the remains of a little girl were found, has returned in addition to the pottery numerous ornaments placed on the chest of the child. The study and analysis of the grave goods has allowed us to highlight how the subadults are the vertical axis through which oikos and society reproduce, passing on heritage, cultural identity and collective memory. The small number of items in the set is not a reflection of the deceased’s condition of marginality, but rather the result of careful selection that defines the status and identity of the young person, and helps to reflect the cultural dynamics of the society of reference.